mNGS helped diagnose scrub typhus-associated HLH in children: a report of two cases - Jian, Hui; Yang, Qiu-xia; Duan, Jia-xin; Lai, Shu-yu; Che, Guang-lu; Teng, Jie; Chang, Li; Liu, Xiao-juan; Luo, Li-li; Liu, Fang (Frontiers in Public Health, 2024)
Background Scrub typhus, caused by the Orientia tsutsugamushi (Ot), is a widespread vector-borne disease transmitted by chigger mites. Hemophagocytic lymphohistiocytosis (HLH) is considered to be one of the potentially severe complications. The diagnosis of scrub typhus-associated HLH may be overlooked due to the non-specific clinical characteristics and the absence of pathognomonic eschar. Case presentation We obtained clinical data from two patients in the South of Sichuan, China. The first case involved a 6-year-old girl who exhibited an unexplained fever and was initially diagnosed with sepsis, HLH, and pulmonary infection. The other patient presented a more severe condition characterized by multiple organ dysfunction and was initially diagnosed with septic shock, sepsis, HLH, acute kidney injury (AKI), and pulmonary infection. At first, a specific examination for scrub typhus was not performed due to the absence of a characteristic eschar. Conventional peripheral blood cultures yielded negative results in both patients, and neither of them responded to routine antibiotics. Fortunately, the causative pathogen Orientia tsutsugamushi (Ot) was detected in the plasma samples of both patients using metagenomics next-generation sequencing (mNGS) and further confirmed by polymerase chain reaction. Subsequently, they both were treated with doxycycline and recovered quickly. Conclusion The unbiased mNGS provided a clinically actionable diagnosis for an uncommon pathogen-associated infectious disease that had previously evaded conventional diagnostic approaches.